Limb motor learning in individuals with Parkinson's disease as a function of practice -- A follow-up pilot experiment to a speech motor learning study. - Kaipa, Ramesh (Clinical Kinesiology (Online Edition))
Purpose: Although, individuals with Parkinson's disease present with motor learning problems, the role of principles of motor learning in learning motor skills has not systematically evaluated in individuals with Parkinson's disease. This pilot study evaluated the role of constant, variable, random, and blocked conditions on spatial and temporal learning of a keyboard task in 16 individuals with Parkinson's disease. Methods: Participants were randomly and equally assigned to one of the four above-mentioned practice conditions. All participants practiced playing a musical keyboard tune for 50 trials on two consecutive days. On the third day, the participants reproduced 5 retention trials of the tune without further practice. Results: The findings revealed that participants did not differ in spatial or temporal learning of the keyboard task as a function of practice condition. Conclusion: Limb motor learning in individuals with Parkinson's disease is likely to be influenced by practice amount instead of the structure of practice condition. However, the results must be extrapolated with caution, as the current experiment is a pilot study. This can have ramifications for developing an evidence-based treatment for individuals with Parkinson's disease.